2014
DOI: 10.5901/mjss.2014.v5n21p147
|View full text |Cite
|
Sign up to set email alerts
|

Generational Sub-cultures: Generation Y a Sub-culture?

Abstract: The aim of this study was to determine (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…Yet different ways of being independent are likely to be associated with selfesteem and life satisfaction in different non-student samples. As previous research suggested, generations are specific types of cultures (Moss and Martins, 2014); therefore, our results might not be the generalized to samples of older adults. Building on the findings of this research regarding the cultural variability in these associations, future studies might therefore test them in both student and nonstudent samples from a wider array of cultural regions.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 71%
“…Yet different ways of being independent are likely to be associated with selfesteem and life satisfaction in different non-student samples. As previous research suggested, generations are specific types of cultures (Moss and Martins, 2014); therefore, our results might not be the generalized to samples of older adults. Building on the findings of this research regarding the cultural variability in these associations, future studies might therefore test them in both student and nonstudent samples from a wider array of cultural regions.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 71%
“…Generation-Y is also constantly exposed to information and communication technologies (Close and Martins, 2015). The South African perspective on Generation-Y employees is that they are good in systems thinking and more counter-intuitive and learning-oriented (Moss, 2014). A study done by Moss (2014) shows that Generation-Y employees are more positive than Generation-X employees regarding strategy and change management, as they have a stronger external locus of control.…”
Section: Resultsmentioning
confidence: 99%
“…Generational subcultures influence the national cultural orientations because the individuals who belong to different generational cohorts have experienced events differently which have influenced their pre-adult years (Ghosh & Chaudhuri, 2009). The generational subcultures are formed within organisations due to the differences in the perceptions of the generational cohorts (Moss & Martins, 2014) and the members of a generational subculture depend on shared aspects like values, beliefs and attitudes which operate as frameworks to enable these members to think, act and lead (Balda & Mora, 2011). The generational subculture approach to examining generations is a significant opportunity for further research (Cox et al, 2014;Lee et al, 2022).…”
Section: Generations As Sub-culturesmentioning
confidence: 99%